Green Transformation of Hrm and Sustainable Development of Organisations - Bernik, Nejc; Šprajc, Polona (Management skozi prizmo digitalnega in zelenega prehoda v družbo 5.0, 2025)
The paper discusses the challenges that will trigger a transformation of HRM in the following years, so-called Green Transformation of HRM (GHRM). The paper presents the results of a survey that addressed the problem of how organizations should proceed to achieve GHRM in the future, using the example of a fundamental HR process such as recruitment. The target group of the respondents of the survey was Generation Z. Generation Z represents the largest generation entering the labour market and is extremely important from a GHRM perspective. The findings of the survey showed that in the future, organizations need to pay more attention to the recruitment of Generation Z in the process of achieving GHRM. Generation Z is attracted to the workplace by the opportunity for teamwork, the personel incomes, and a good organizational climate. When organizations will achieve GHRM, they will achieve social sustainability.